Idiopathic pulmonary fibrosis: current treatment options and critical appraisal of nintedanib - Bonella F; Stowasser S; Wollin L (Dove Medical Press, 2015)
Francesco Bonella,1 Susanne Stowasser,2 Lutz Wollin3 1Interstitial and Rare Lung Disease Unit, Ruhrlandklinik, University Hospital, University of Duisburg-Essen, Essen, 2Boehringer Ingelheim Pharma GmbH & Co. KG, Ingelheim am Rhein, 3Boehringer Ingelheim Pharma GmbH & Co. KG, Biberach an der Riss, Germany Abstract: Idiopathic pulmonary fibrosis (IPF) is the most common type of idiopathic interstitial pneumonia and is characterized by a poor prognosis, with an estimated 5-year survival of approximately 20%. Progressive and irreversible lung functional impairment leads to chronic respiratory insufficiency with a severely impaired quality of life. In the last 2 decades, novel treatments for IPF have been developed as a consequence of an increasing understanding of disease pathogenesis and pathobiology. In IPF, injured dysfunctional alveolar epithelial cells promote fibroblast recruitment and proliferation, resulting in scarring of the lung tissue. Recently, pirfenidone and nintedanib have been approved for the treatment of IPF, having shown efficacy to slow functional decline and disease progression. This article focuses on the pharmacologic characteristics and clinical evidence supporting the use of nintedanib, a potent small-molecule tyrosine kinase inhibitor, as therapy for IPF. After introducing the mechanism of action and pharmacokinetics, an overview of the safety and efficacy results from the most recent clinical trials of nintedanib in IPF is presented. Keywords: tyrosine kinase, disease progression, treatment outcome, usual interstitial pneumonia, therapeutics